Copeptin levels in patients with vasovagal syncope - Flevari,P.; Leftheriotis, D; Kroupis, C.; Antonakos, G.; Lekakis, J.; Dima, K. (Int.J.Cardiol., 2017)
BACKGROUND AND PURPOSE: Vasovagal syncope (VVS) is linked to more than one pathophysiologic mechanisms. Copeptin, an emerging cardiovascular marker, is a surrogate for arginine-vasopressin, which increases following VVS. We aimed to assess the dynamic pattern of copeptin levels in typical VVS, categorized by the degree of vasoconstriction during orthostasis, and healthy controls. METHODS: The following groups were studied: Group A (n=21), with adequate limb vasoconstriction during the first min. of tilt, assessed by limb plethysmography (at least 30% flow reduction); Group B (n=15), showing impaired vasoconstriction during orthostasis (<10% reduction); Group C (n=18), history of VVS and negative tilt test result; Group D (n=18), healthy controls. Copeptin plasma levels were assessed before and 5min following tilt test positivity or termination. RESULTS: Baseline copeptin values were similar in all groups (8.3+/-6.4 in Group A, 5.7+/-2.3pmol/l in B, 6.0+/-1.9 in C, and 6.9+/-2.6 in D, p: 0.41). Significant increases in copeptin during tilt were observed in all Groups of VVS patients (A, B, C), including those with negative tilt (Group C: from 6.0+/-1.9 to 27.7+/-12.6pmol/l, p: 0.001), but not in controls. Following tilt termination, a greater increase was observed in copeptin values in Group B vs all other Groups A, C, and D (111.6+/-63.5 vs 29.5+/-51.3, 27.7+/-12.6, and 8.3+/-2.9, respectively). CONCLUSIONS: Copeptin increases following tilt not only in VVS with a positive response, but also in typical history patients with a negative test. Increased copeptin levels following orthostasis may be useful for diagnosing VVS
Keywords: Biomarkers; Blood; Diagnosis; Electrocardiography; Female; Follow-Up Studies; Glycopeptides; Greece; Heart Rate; Humans; Male; Middle Aged; physiology; physiopathology; Plethysmography; Protein Precursors; Retrospective Studies; Syncope,Vasovagal; Tilt-Table Test; Vasoconstriction